Green Product and Corporate Social Responsibility Influence Purchasing Decisions Mediated By The Body Shop Consumers' Purchase Interests In Bandung - Nasuha, Aufa Fitriannauroh; Paramita, Veronika Santi (Commercium : Journal of Business and Management, 2025)
This research aimed to determine the effect of green products and corporate social responsibility on purchasing decisions, using intention as a mediating variable of The Body Shop beauty brand in Bandung. This is due to the significant continuous decline in sales results for The Body Shop brand. The sales revenue of the British cosmetics, skincare, and perfume company The Body Shop has tended to decline from 2016 to 2022. The Body Shop has provided environmentally friendly products and always improves the company's quality and value through environmental issues caused by shifts in consumer demand. However, this did not increase revenue from sales made by The Body Shop. The instrument used in this study was carried out after the instrument was declared to have passed. The data is based on the questionnaires distributed and then analyzed using descriptive tests, classical assumption tests, multiple regression tests, Sobel tests, and hypothesis tests. The results of this study state that green products and corporate social responsibility significantly influence purchasing decisions through purchasing interest. It is important to utilize the knowledge that purchasing decisions can be influenced by several variables that influence them. Green products and corporate social responsibility can influence low purchasing decisions. With these variables, it can encourage consumer interest in purchasing products. Therefore, decision-makers at The Body Shop can increase purchasing interest by improving and enhancing the green products they have and the corporate social responsibility programs they carry out.